Evaluasi Kebutuhan Angkutan Angkutan Umum Penumoang Kota Malang (Studi Kasus Rute Arjosari-Dinoyo-Landungsari) - Abadi, Khoirul; Ruskandi, Ruskandi (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2016)
Public transport passengers in Malang called angkot is one of the means of transportation that allows people to perform daily activities, but transport is increasingly interested in the community due to the low level of services, so that many people to using private vehicles. The fleet of public transport passengers (FPTP) routes ADL is currently 118 units with a capacity of 12 passenger/vehicle. Purpose of this study is to determine the performance, productivity and the needs of FPTP ADL optimal trajectory in the city of Malang. The method used in this study adopts the Technical Guidelines for the Implementation of Public Transport in Cities in Fixed Route and Regular (Direktorat Jendral Perhubungan Darat 2002) and using empirical formulations. The study of public transport performance passenger route ADL in 2015, the average load factor of 97.06%, the average frequency of 23.56 vehicle/hour, average headway time of 2.60 minutes, the average travel time 4,10 min/km, average travel speed of 15.03 km/hour. The average productivity of 55 passenger/day-vehicle with optimal fleet size is 116 units.